PENGARUH KARAKTERISTIK SISTEM AKUNTANSI MANAJEMEN (SAM) TERHADAP KINERJA MANAJERIAL DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI - I Kadek Yoga Pratama (Hita Akuntansi dan Keuangan, 2021)
Increasing managerial performance in a company or organization can be achieved by means of the manager of the company or organization taking advantage of the ability to see and take advantage of opportunities, identify problems, and select and implement adaptation processes in a particular company or organization. The purpose of thissstudy wastto determine the effect of theecharacteristics0offthe management accounting system(SAM) on managerial performance with locus of control as a moderating variable. This research was conducted in LPDs throughout Susut District, Bangli, with a total sample of 55 people. The samplingi method usedl was nonprobability sampling, namelylpurposive sampling, while tthe data analysisi techniques used were validityy test, reliability test, classical assumption test, moderated regression analysis (MRA) test, (R2), F test, t test. The results showed that: (1) The characteristics of the management accounting system have a positive and significant effect on managerial performance variables. (2) Locus of control does not moderate the effect of the characteristics of the management accounting system on managerial performance.